2016
DOI: 10.1186/s12940-016-0101-8
|View full text |Cite
|
Sign up to set email alerts
|

Reducing burden of disease from residential indoor air exposures in Europe (HEALTHVENT project)

Abstract: BackgroundThe annual burden of disease caused indoor air pollution, including polluted outdoor air used to ventilate indoor spaces, is estimated to correspond to a loss of over 2 million healthy life years in the European Union (EU). Based on measurements of the European Environment Agency (EEA), approximately 90 % of EU citizens live in areas where the World Health Organization (WHO) guidelines for air quality of particulate matter sized < 2.5 mm (PM2.5) are not met. Since sources of pollution reside in both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 19 publications
0
60
0
2
Order By: Relevance
“…In Asia, cooking and heating with solid fuels are the main sources of indoor air pollution, whereas in Europe, several sources contribute to indoor pollution, such as volatile organic compounds from organic solvents, household products and PM from cooking and wood burning. Nevertheless, a recent European study demonstrated that 60% of the global burden of indoor air pollution-related disease comes from outdoor PM 2.5 penetrating inside via air exchange [4]. Consequently, decreasing the burden of disease from indoor air pollution requires measures that affect indoor air pollution sources, ventilation and filtration of outdoor air [4].…”
Section: Air Pollution Basicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Asia, cooking and heating with solid fuels are the main sources of indoor air pollution, whereas in Europe, several sources contribute to indoor pollution, such as volatile organic compounds from organic solvents, household products and PM from cooking and wood burning. Nevertheless, a recent European study demonstrated that 60% of the global burden of indoor air pollution-related disease comes from outdoor PM 2.5 penetrating inside via air exchange [4]. Consequently, decreasing the burden of disease from indoor air pollution requires measures that affect indoor air pollution sources, ventilation and filtration of outdoor air [4].…”
Section: Air Pollution Basicsmentioning
confidence: 99%
“…Nevertheless, a recent European study demonstrated that 60% of the global burden of indoor air pollution-related disease comes from outdoor PM 2.5 penetrating inside via air exchange [4]. Consequently, decreasing the burden of disease from indoor air pollution requires measures that affect indoor air pollution sources, ventilation and filtration of outdoor air [4]. …”
Section: Air Pollution Basicsmentioning
confidence: 99%
“…Indoor exposures have been estimated to cause a substantial loss of health in Europe, representing ca. 2 million healthy life years . The burden is dominated by particulate matter in residencies, but also includes a contribution from volatile organic compounds (VOCs).…”
Section: Introductionmentioning
confidence: 99%
“…2 million healthy life years. 6 The burden is dominated by particulate matter in residencies, but also includes a contribution from volatile organic compounds (VOCs). However, this burden is poorly estimated, not considering specific VOCs and their toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Urge-Vorsatz et al 2016 paper reviewed monetized multiple benefits of building energy efficiency measures and confirmed that in the few studies having a comprehensive account of non-energy multiple benefits, productivity improvements score high. 4 Recent work demonstrates that breathing air in buildings is responsible for a very significant loss of life and disability even in Europe (Asikainen et al 2016). Many studies show how indoor air quality can cause several diseases such as asthma, cold, flu, allergy, and even cardiovascular diseases and cancer (Fisk 2000;Fisk 2002;Mudarri and Fisk 2007;Asikainen et al 2016).…”
Section: Higher Work Productivitymentioning
confidence: 99%